Deciphering the mechanisms and effects of hyperglycemia on skeletal muscle atrophy - Khushboo Gaur; Lucy Mohapatra; Pranay Wal; Amana Parveen; Shivam Kumar; Vaishali Gupta (Metabolism Open)
Hyperglycemia, a hallmark of diabetes mellitus, significantly contributes to skeletal muscle atrophy, characterized by progressive muscle mass and strength loss. This review summarizes the mechanisms of hyperglycemia-induced muscle atrophy, examines clinical evidence, and discusses preventive and therapeutic strategies. A systematic search of electronic databases, including PubMed, Scopus, and Web of Science, was conducted to identify relevant papers on hyperglycemic skeletal muscle atrophy. Key mechanisms include insulin resistance, chronic inflammation, oxidative stress, and mitochondrial dysfunction. Crucial molecular pathways involved are Phosphoinositide 3-kinase/Protein kinase B signaling, Forkhead box O transcription factors, the ubiquitin-proteasome system, and myostatin-mediated degradation. Hyperglycemia disrupts normal glucose and lipid metabolism, exacerbating muscle protein degradation and impairing synthesis. Clinical studies support the association between hyperglycemia and muscle atrophy, emphasizing the need for early diagnosis and intervention. Biomarkers, imaging techniques, and functional tests are vital for detecting and monitoring muscle atrophy in hyperglycemic patients. Management strategies focus on glycemic control, pharmacological interventions targeting specific molecular pathways, nutritional support, and tailored exercise regimens. Despite these advances, research gaps remain in understanding the long-term impact of hyperglycemia on muscle health and identifying novel therapeutic targets. The review aims to provide a comprehensive understanding of the mechanisms, clinical implications, and potential therapeutic strategies for addressing hyperglycemia-induced skeletal muscle atrophy.